SIAGA-Flytrap: Pengembangan Alat Peraga IPA Bermuatan STEAM-Biomimikri untuk Menunjang Pembelajaran Mekanisme Gerak Tumbuhan Siswa SMP/MTs - Bunga Avelia Fasah; Iseu Laelasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Technology, Engineering, Art and Mathematics) with the principle of biomimicry. The method in this study uses the Research and Development model with the 4D model (Define, Design, Develop, Desseminate). The subjects of the limited trial were students of grade VIII students of SMPN 2 Grobogan. Data collection techniques include observation, interviews, media and material validation questionnaires, as well as teacher and student response questionnaires. Analysis data analysis was carried out quantitatively and qualitatively descriptive. The validation results showed that SIAGA-Flytrap props get a very feasible category for each indicator and aspect in media and material validation, as well as teacher and student response questionnaires indicators and aspects in media and material validation, as well as the results of teacher response questionnaires. Response questionnaire results obtained an average score of 3.00 and 3.18 students, both of which were included in the good category good category. The response of teachers and students to the teaching aids is also very positive, and by using these teaching aids, it provides a very good learning experience and by using this teaching aid provides a more enjoyable and meaningful learning experience more fun and meaningful.